2017
DOI: 10.4081/ejh.2017.2837
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and vitamin D receptor in patients with ophthalmic pterygium

Abstract: Pterygium, an ultraviolet radiation (UV)-related disease, is a relatively benign process, but since it displays tumor-like features, it has been proposed to be a neoplastic-like growth disorder. Vitamin D performs a number of functions in addition to calcium homeostasis, as inhibition of cell proliferation, activation of apoptotic pathways, and inhibition of angiogenesis. Since the antitumor actions of vitamin D are mediated primarily through the nuclear vitamin D receptor (VDR), the aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The variant does not determine structural alterations of the protein, but the presence of the G allele (b) affects the polyadenylation of the transcript, influencing the stability of mRNA and therefore modifying the protein expression. However, several meta-analyses have only shown that the G (b) allele showed lower but not significant bone mass density values [ 24 , 31 ]. Regarding TaqI polymorphism, our results are in line with those obtained in previous studies of Italian subjects with periodontitis in which T (T) allele were higher in patients than in controls, although in some previous works on Caucasian population the C (t) allele seems to increase the risk of developing periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variant does not determine structural alterations of the protein, but the presence of the G allele (b) affects the polyadenylation of the transcript, influencing the stability of mRNA and therefore modifying the protein expression. However, several meta-analyses have only shown that the G (b) allele showed lower but not significant bone mass density values [ 24 , 31 ]. Regarding TaqI polymorphism, our results are in line with those obtained in previous studies of Italian subjects with periodontitis in which T (T) allele were higher in patients than in controls, although in some previous works on Caucasian population the C (t) allele seems to increase the risk of developing periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…This variant determines the creation of a new start codon at three amino acids downstream from the site of initiation of translation, with consequent alteration of the related protein. The C (F) variant therefore induces the synthesis of a shorter protein with greater biological activity and more effective in the transcriptional activity of the vitamin D signal [ 31 , 35 ]. The TT + CT+ (ff +Ff) genotypes are associated with lower bone mineral density than the CC (FF) genotype, as available on the Pharmacogenomics Knowledgebase (PharmGKB) (PharmGKB ID: 769164470) [ 54 ] and confirmed by a recent meta-analysis published this year conducted on 14 studies with 2219 participants [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 52 pterygium samples, 48 specimens were 10% formalin-fixed and paraffinembedded; moreover, 11 epibulbar conjunctiva specimens, belonging to a group of 15 samples from healthy donors, were formalin-fixed, processed for paraffin embedding, and used as normal controls. Three microtome histological sections (6-7 µm thick) per sample were subjected to immunohistochemistry (IHC) for the demonstration of IGF-2 and IGF-1R antigens using the streptavidin-biotin alkaline phosphatase method, as previously described [7,53]. These were dewaxed, rehydrated, and rinsed in phosphate-buffered saline (PBS), pH 7.4.…”
Section: Immunohistochemical (Ihc) Analysismentioning
confidence: 99%
“…In healthy conjunctiva, VDR was localized mainly in the cytoplasm, while in pterygium cells, VDR was co-localized in the nucleus and cytoplasm. Hence, the nuclear signaling pathways related to VDR may be engaged in the pathogenesis of pterygium [ 183 ]. Further analyses and clinical trials are needed to standardize the role of VDR in pathogenesis and the development of pterygium.…”
Section: Vitamin D Vdr and Calcitriol Analogues In Ocular Diseasesmentioning
confidence: 99%